Morphology, Phase and Photoluminescence of ZnS Microstructures Grown by Thermal Deposition at Different Temperature of Substrates - Nguyen Van, Nghia; Hung, Nguyen Duy (VNU Journal of Science: Mathematics - Physics, 2017)
ZnS microstructures were prepared by thermal evaporating ZnS powder in Ar gas ambient at atmospheric pressure. The influent of temperature at the possitions puted the silica substrates on morphology, phase and photoluminescence of ZnS was investigated. It is clearly seen from the X-ray diffraction pattern  that there is only ZnS phase with hexagonal structures at high temperature. Whereas, both ZnS and ZnO appear at lower temperature areas. The morphology of the microstructures change depending on substrate temperatures. The photoluminescence spectrum (PL) at room temperature shows that there is the shift from ultraviolet (UV) emission at high substrate temperature to strong blue emission at lower substrate temperature. The origin of these bands will be discussed in detail.